PENERAPAN MYOB DALAM PENCATATAN LAPORAN KEUANGAN UMKM ABADI CELL LAMPUNG TIMUR - Tina Miniawati Barusman; Veronika Saptarini; Evelyn Felicia Setiawan (Jurnal Manajemen dan Bisnis, 2025)
This study aims to determine how the implementation of MYOB Accounting software-based financial report preparation at MSME Abadi Cell and assess the quality of the resulting financial reports based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Before using MYOB, MSME Abadi Cell still conducted financial records manually using Microsoft Excel and sales notes, so the prepared financial reports were incomplete and not presented systematically. This condition makes the resulting financial information less than optimal as a basis for decision making. The research method used is a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation of MSME activities and financial documents. The results show that the implementation of MYOB Accounting software can increase the effectiveness and efficiency in recording financial transactions. In addition, the use of MYOB also produces more structured financial reports, including the statement of financial position, income statement, and cash flow statement. To complement the reports generated by MYOB, the preparation of notes to the financial statements (CALK) is done manually. This CALK serves to provide explanations regarding accounting policies, recognition and measurement of key accounts, and the calculation of MSME income tax. Thus, the financial reports after the implementation of MYOB are considered more informative, transparent, and in accordance with the provisions of SAK EMKM, so that they can support managerial decision making at MSME Abadi Cell.